2007
DOI: 10.1111/j.1365-2966.2007.11954.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing the accuracy of synthetic stellar libraries

Abstract: One of the main ingredients of stellar population synthesis models is a library of stellar spectra. Both empirical and theoretical libraries are used for this purpose, and the question about which one is preferable is still debated in the literature. Empirical and theoretical libraries are being improved significantly over the years, and many libraries have become available lately. However, it is not clear in the literature what are the advantages of using each of these new libraries, and how far behind models… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
90
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(104 citation statements)
references
References 76 publications
12
90
2
Order By: Relevance
“…McWilliam et al 2008). Martins & Coelho (2007) find for the C-dominated features that the difference between the theoretical and empirical stars is emphasised for stars cooler than ≃ 4500 K. These stars have a large impact on the old SSPs represented in Fig. 5.…”
Section: Truly Scaled-solar and α-Enhanced Modelsmentioning
confidence: 95%
See 3 more Smart Citations
“…McWilliam et al 2008). Martins & Coelho (2007) find for the C-dominated features that the difference between the theoretical and empirical stars is emphasised for stars cooler than ≃ 4500 K. These stars have a large impact on the old SSPs represented in Fig. 5.…”
Section: Truly Scaled-solar and α-Enhanced Modelsmentioning
confidence: 95%
“…The Coelho et al (2005) theoretical library covers effective temperatures, T eff , between 3500 and 7000 K, surface gravities, log g, between +0.0 and +5.0, iron metallicities, [Fe/H] The accuracy of this library has been assessed in Martins & Coelho (2007), who showed that this library had the highest success in reproducing spectral features of observed stars among the theoretical libraries analysed in that work. The spectra have higher spectral resolution and wavelength coverage than MILES, therefore they were convolved with a gaussian kernel and were resampled to match MILES spectral resolution, dispersion and wavelength coverage.…”
Section: Theoretical Stellar Spectral Librarymentioning
confidence: 99%
See 2 more Smart Citations
“…The pros and cons of either approach are discussed extensively in the literature (e.g., Gustaffson et al 2007;Martins & Coelho 2007).…”
Section: Spectral Librariesmentioning
confidence: 99%